Flight control system evaluation based on multiple metrics - Yashvin Beni (2016)
Fly-by-wire control system has Ied to the advancement of the field of aviation in terms of performance and safety. However the problems linked to poor design has been the root cause of numerous accidents. In an attempt to address the critical issues linked to flight control design, an exhaustive array of established guidelines has been put into practice so as to verify, correct and prevent the occurrence of these events during the preliminary control design process. This thesis contributes to the in-depth assessment of an extensive set of flight control metrics which intends to identify and predict the possible design flaws of a Physical Dynamic Inversion controller for the Diamond DA-42 Twin Star general aviation aircraft. Additionally, a comprehensive set of flying criterion was validated with the military aviation standards and was successfully applied to the aircraft system model under development. The first metric includes a Lower Order Equivalent System (LOES) technique which permits the comparison of highly augmented complex control systems with the existing military standard while at the same time fulfilling the tolerance limits of the Maximum Unnoticeable Added Dynamics (MUAD). It was successfully applied to the minimisation of the high order pitch attitude and Ioad factor transfer functions of the Dl based flight control system, yielding a mismatch error of 0.7979 and 1.2051 respectively. In the context of category Il Pilot Induced Oscillation (PIO), a comparative case study analysis of the past PIO prone accidents was investigated. The risks of PIO for the controller under development were outlined by means of an OLOP criterion. The findings reveal the DA^f2's susceptibility to Pilot Induced Oscillation. The controller gains were subsequently reduced and the results demonstrate that the risk of PIO is substantially decreased. Besides this, by means of a Ioop cutting technique, the phase and gain margin were evaluated at different locations on the Dl based flight control system. It was observed that the stability margin requirements were fulfilled for the nominal case and the safety margin started to degrade with increase in time delay. The impact of uncertainties on the stability margin were also analysed with the results showing a non-violation of the exclusion zones. Furthermore, the influence of noise and disturbances on the Dl plant’s performance was also studied with the results revealing adequate robustness against disturbances. For the case of noise rejection, the plant also displayed adequate noise attenuation characteristics except for the case of the pitch rate command. The use of weighing filters was recommended to shape the complementary sensitivity response according to the desired requirements. Finally, using a robust control approach, the sensitivity of the dynamic inversion based flight control system with respect to parametric variations was evaluated. The results demonstrate reasonable robustness characteristics of the DA^t2 general aviation model with a parametric sensitivity of up to 25 %.